Recipes for bio fortified rice/wheat biscuits - CGIAR Research Program on Rice (2019)
Recipes have been developed, biscuits have been produced and characterized through sensory evaluation. Storage experiments have been conducted and small-scale processors especially women groups have been trained on biscuit production and commercialization.